RT-based combination therapy for brain metastasis from NSCLC with non-EGFR mutation/ALK gene rearrangement: A network meta-analysis - Wu, Min; Jiang, Jun; Zhang, Xuewen; Chen, Jie; Chang, Qiaomei; Chen, Rong (Frontiers in Oncology, 2022)
Radiotherapy (RT) is currently the main treatment for brain metastases (BMs) from non-small cell lung cancer (NSCLC). Due to the short survival time and obvious adverse reactions of RT, we urgently need more appropriate treatment. This Bayesian network meta-analysis reviewed the efficacy and adverse effects of radiotherapy-based combination therapy for patients without targeted epidermal growth factor receptor (EGFR) mutations /anaplastic lymphoma kinase (ALK) gene rearrangement NSCLC BMs, to screen out the therapy with the best efficacy. PubMed, Embase, Web of Science, and Cochrane Library were searched from the earliest publication date available to 1 April 2022. STATA15.0 was used to conduct heterogeneity analysis, sensitivity analysis, forest plot analysis, and publication bias analysis. A total of 28 studies, involving 3707 patients were included in the Bayesian network meta-analysis. In the limited paired meta-analysis for head-to-head comparative trials, compared with RT-based combination therapy, RT combined with Immune checkpoint inhibitors (ICIs) showed significant overall survival (OS) benefit (HR 0.65, 95%CI 0.47–0.9, p<0.01), RT combined with ICIs showed a non-significant difference for intracranial progression-free survival (iPFS) (HR 0.76, 95%CI 0.27–2.27, p<0.01) and progression-free survival (PFS) (HR 0.9, 95%CI 0.36–2.37, p<0.01). In addition, according to the ranking results, compared with RT combined with chemotherapy(CT) or with targeted therapy(TT), RT combined with ICIs might be the best treatment mode for OS（ICIs+RT vs CT+RT vs TT+RT; 91.9% vs. 27.8% vs. 29.3%）, iPFS (ICIs+RT vs CT+RT vs TT+RT, 46.9% vs 25.2% vs 25.6%) and PFS (ICIs+RT vs CT+RT vs TT+RT, 36.2% vs 31% vs 36.5%). RT combined with ICIs might be the best treatment mode to prolong the OS for BMs from NSCLC with non-EGFR mutation/ ALK gene rearrangement.